An analysis of JIT from the Perspective of Environmental Sustainability - Melo, Julio Cesar; Bezerra, Barbara Stolte; de Souza, Fernando Bernardi (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – The fundamental concept behind Just in Time (JIT) is to provide the right product at the right time and in the required quantity, reducing inventories in warehouses and in manufacturing processes. On the other hand, it requires increased usage of transport vehicles, which may negatively affect the organization's environmental sustainability indicators. In order to contribute to discussions on the subject, this study aims to identify, systematize and analyze the available literature on the intersection of JIT and Environmental Sustainability topics. Design/methodology/approach – A structured literature review was performed through research in the Scopus and Web of Science databases. Fifty-three papers published in journals or at congresses were identified and analyzed. Findings – The selected papers were categorized in five dimensions: environmental aspects, operational costs, operational performance, research method and location/region of the study. A lack of consensus was identified on whether or not logistics operations favor sustainable practices that used the JIT system. Originality/value – To build on the analysis and discussions on the JIT and Environmental Sustainability and support future research on the subject, the study has classified 53 selected papers based on their purposes in five different dimensions. Given that organizations need to become increasingly sustainable, a SWOT (strengths, weaknesses, opportunities, and threats) matrix has been prepared in addition. Keywords - Just In Time, Transport, Environment; Sustainability; Logistics.